Inducible protein stabilization system in Leishmania mexicana - Podešvová, Lucie; Huang, Huan; Yurchenko, Vyacheslav (Molecular and biochemical parasitology, 2017)
Targeted regulation of protein levels is an important tool to investigate the role of proteins essential for cell function and development. In recent years, methods based on the Escherichia coli dihydrofolate reductase destabilization domain (ecDHFR DD) have been established and used in various cell types. ecDHFR DD destabilizes the fused protein of interest and causes its degradation by proteasomes, unless it is stabilized by a specific ligand, trimethoprim. In this work we developed an inducible protein stabilization system in Leishmania mexicana based on ecDHFR DD.
Keywords: aktivace transkripce; Leishmania mexicana; Gene Expression Regulation; Molecular Biology; Recombinant Proteins; rekombinantní proteiny; Parasitology; dihydrofolátreduktasa; Tetrahydrofolate Dehydrogenase; Transcriptional Activation; parazitologie; Escherichia coli; ecDHFR; Protein stabilization; trimethoprim; regulace genové exprese; molekulární biologie; Trimethoprim